ANALISIS PERBANDINGAN KINERJA KEUANGAN ANTARA PERBANKAN KONVENSIONAL DENGAN PERBANKAN SYARIAH DI INDONESIA - Marbelanty, Fivtina; Adityawarman, Adityawarman (Diponegoro Journal of Accounting, 2015)
Currently there are many Islamic banks in Indonesia as a form of concern for the banking industry with a selection of the bank in accordance with the Islamic shari’a. Many conventional banks began to open Islamic branches, so that the majority of Indonesian people who are Muslim may use the services of the bank without having to fear about riba. This study aimed to compare the financial performance of the two types of banks. This study used liquidity ratios, profitability ratios, risk and solvency ratio, as well as the efficiency ratio to measure financial performance.This study used secondary data documentation, by looking at the financial statements (annual report) banks during the period 2011-2013 were taken from the website of each bank. Samples were taken using purposive sampling method with the criteria specified by the author. The number of samples obtained from the criteria which are 21 banks with a total of 62 samples. Hypothesis testing using Financial Ratio Analysis (FRA).The results showed there were significant differences in the financial performance of conventional banks and Islamic banks. However, the overall financial performance of conventional banks and Islamic banks were equally good, because conventional banks better in the ratio of profitability and efficiency ratios, while Islamic banks better in liquidity ratio and the risk and solvency ratio.